The Effect of Vitamin E Administration on the Profile of Hypoxia-Inducible Factor-1 Alpha (Hif-1α) and Vascular Endothelial Growth Factor (VEGF) in Intraperitoneal Adhesion - Sudirman, Taufik; Hatta, Mochammad; Prihantono, Prihantono; Bukhari, Agussalim; Tedjasaputra, Tjahjadi Robert; Warsinggih, Warsinggih; Labeda, Ibrahim; Bahar, Burhanuddin; Lie, Hendry (Journal of Neonatal Surgery, 2025)
Introduction: Intraperitoneal adhesions are a common complication following surgical procedures, often leading to significant morbidity and healthcare costs. These adhesions are associated with hypoxia-induced pathways, including the upregulation of hypoxia-inducible factor-1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF), which play critical roles in inflammation and angiogenesis during tissue repair. Vitamin E, known for its antioxidant properties, has been proposed as a potential therapeutic agent to mitigate adhesion formation. This study aims to explore the effects of vitamin E administration on the mRNA expression of HIF-1α and VEGF genes, their protein levels, and the subsequent impact on intraperitoneal adhesion formation in an animal model. Methods: This experimental study utilized 20 three-month-old Wistar strain Rattus norvegicus rats, divided into four groups: (1) sham-operated group, (2) placebo group, (3) intraperitoneal administration of vitamin E combined with olive oil, and (4) oral administration of vitamin E. Blood samples were collected on day one (pre-laparotomy), day three, and day fourteen to measure the mRNA expression of HIF-1α and VEGF genes. On day fourteen, a relaparotomy was performed to collect adhesion tissue for macroscopic and microscopic evaluation. Statistical analysis was conducted to compare the outcomes across the groups, with a significance level set at p < 0.001. Results: The results demonstrated that intraperitoneal administration of vitamin E combined with olive oil significantly inhibited the increase in HIF-1α and VEGF mRNA expression and protein levels while preventing the formation of intraperitoneal adhesions compared to the sham and placebo groups (p < 0.001). Oral administration of vitamin E also suppressed the elevation of HIF-1α and VEGF expression and protein levels but was less effective than intraperitoneal administration. Nevertheless, both routes of administration showed significant anti-adhesion effects compared to the control groups. Conclusion: Intraperitoneal administration of vitamin E combined with olive oil exhibits a potent anti-adhesion effect in Rattus norvegicus by reducing the incidence and severity of intraperitoneal adhesions. This effect is mediated through the suppression of HIF-1α and VEGF gene expression and protein levels, highlighting the therapeutic potential of this combination in mitigating post-surgical adhesion formation. While oral vitamin E also shows promise, its efficacy is comparatively lower than intraperitoneal administration. These findings warrant further investigation in clinical settings to validate their translational potential.